2022
DOI: 10.3390/catal12101117
|View full text |Cite
|
Sign up to set email alerts
|

Integrated p-n Junctions for Efficient Solar Water Splitting upon TiO2/CdS/BiSbS3 Ternary Hybrids for Improved Hydrogen Evolution and Mechanistic Insights

Abstract: The development of efficient and novel p-n heterojunctions for photoelectrochemical (PEC) water splitting is still a challenging problem. We have demonstrated the complementary nature of (p-type) BiSbS3 as a sensitizer when coupled with (n-type) TiO2/CdS to improve the photocatalytic activity and solar to hydrogen conversion efficiency. The as-prepared p-n heterojunction TiO2/CdS/BiSbS3 exhibits good visible light harvesting capacity and high charge separation over the binary heterojunction, which are confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The excited electrons migrate from the VB (1.07 eV vs RHE) to the CB (−0.55 eV vs RHE) of CIS NSAs. Incorporating an overlayer of n-type CdS having the CB and VB at −0.50 eV vs RHE and 1.70 eV vs RHE gives rise to a p–n junction, resulting in the transfer of photogenerated electrons in the CIS NSA CB to CB of CdS. Then, electrons are transferred to the noble metal-free co-catalyst MoS 2 having CB and VB positions −0.23 eV vs RHE and 1.71 eV vs RHE, respectively, providing surface active sites to the H + ions for adsorption and getting reduced to H 2 with the photoexcited electrons .…”
Section: Resultsmentioning
confidence: 99%
“…The excited electrons migrate from the VB (1.07 eV vs RHE) to the CB (−0.55 eV vs RHE) of CIS NSAs. Incorporating an overlayer of n-type CdS having the CB and VB at −0.50 eV vs RHE and 1.70 eV vs RHE gives rise to a p–n junction, resulting in the transfer of photogenerated electrons in the CIS NSA CB to CB of CdS. Then, electrons are transferred to the noble metal-free co-catalyst MoS 2 having CB and VB positions −0.23 eV vs RHE and 1.71 eV vs RHE, respectively, providing surface active sites to the H + ions for adsorption and getting reduced to H 2 with the photoexcited electrons .…”
Section: Resultsmentioning
confidence: 99%
“…As exhibited in Figure 5c, with the extended amount of MC photocatalysts from 10 mg to 50 mg, the HER rate of the heterojunction system first increased then decreased. Under a photocatalytic HER reaction, owing to the charge carrier production step, both charge carrier transporting and trapping are required situations [28]. Redundant MC-4 samples arise to be significantly agglomerated and appear to be further from the crystal boundary, ultimately affecting the serious electrons and holes' recombination rate, which reduces the operation of the photocatalysts.…”
Section: Photocatalytic Hydrogen Evolution and Stabilitymentioning
confidence: 99%
“…The technology to convert water into hydrogen fuel using sunlight was shown to be effective by photoelectrochemical (PEC) cells with photoelectrodes, which are easy to transport and do not produce greenhouse gases. This is a promising method for utilizing solar energy to create chemical energy in the form of hydrogen fuel. PEC water splitting utilizing numerous semiconductor materials has been widely investigated as a significant effort to harness solar energy. Since Fujishima and Honda demonstrated that TiO 2 has a photocatalytic function, various semiconductor materials have been explored to enhance the STH efficiency and photostability in PEC water splitting. PEC cell reactions are performed using a three-electrode system, where the semiconductor photoelectrode acts as the working electrode, a metal rod such as Pt serves as the counter electrode, and Ag/AgCl acts as the reference electrode. In such a three-electrode system, the working electrode only drives one of the two half-reactions of water splitting. The other half-reaction is usually driven by an external bias applied to the counter electrode. In the real-world application, PEC cells would be set up using a two-electrode configuration for water splitting, ideally without the use of a physical bias. Instead of the expensive Pt, BiVO 4 can be used as a more effective, affordable, and environmentally friendly photocatalyst for water splitting.…”
Section: Introductionmentioning
confidence: 99%